Valorization of the Liquid Fraction of Co-Hydrothermal Carbonization of Mixed Biomass by Anaerobic Digestion: Effect of the Substrate to Inoculum Ratio and Hydrochar Addition - Huilinir-Curio, C; Pages-Diaz, J (Elsevier Ltd, 2020)
The effect of the substrate to inoculum ratio (SIR) on the anaerobic digestion (AD) of the liquid fractions (LFs) of co-hydrothermally treated mixed biomass (sewage sludge (SS) and the organic fraction of municipal solid waste (MSW)) was evaluated. The impact of SS + MSW-hydrochar was also studied at different hydrochar concentrations (0, 1, 5, 10, 15, 20 and 25 ghydrochar/L), in two of the LFs studied. The SIR had a significant impact on methane yield (YCH4) and organic matter degradation, with low methane production (4–44 NmLCH4/g tCODadded) observed for all LFs at SIR = 1:3. Hydrochar significantly improved YCH4 and specific methane production rate. Compared with the AD without hydrochar, the YCH4 improved up to 1.95 times at 15 g/L. Hydrochar doses from 1 to 10 g/L shortened the lag phase, while higher concentrations (15 to 25 g/L) showed an increment with respect to the control reactor without hydrochar. © 2020 Elsevier Ltd